Síntese de derivados de chalconas e de 2-quinolinonas visando a busca por inibidores das enzimas cruzaína e da família BET bromodomain - Vieira, Lucas Campos Curcino (Universidade Federal de São Carlos, 2014)
The first part of this work involved the synthesis of chalcone derivatives towards the development of inhibitors of the enzyme cruzain from Trypanosoma cruzi. Different green chemistry approaches were employed to functionalize chalcones as the use of alternative solvents as well as source of energy. A new Suzuki cross-coupling methodology for synthesis of functionalized chalcones was developed, employing PEG-400 as solvent under microwave irradiation. The use of organocatalysis in the 1,4-addition of α,α-dicyanoolefins to α,β- unsaturated carbonyl system provided products with good yields and excellent enantiomeric excess. It was also developed a new synthetic route for the synthesis of γ-butenolides from chalcones. The key step was accomplished using montmorillonite K10 clay as catalyst and ethanol as solvent... (CONTINUE)
Synthesis of chalcone and 2-quinolinone derivatives towards the development of new cruzain and BET bromodomain enzyme inhibitors
Keywords: Síntese orgânica; Chalconas; 2-quinolinonas; Suzuki, Acoplamento de; Organocatálise; Cruzaína; CIENCIAS EXATAS E DA TERRA::QUIMICA